Pemanfaatan Kombinasi Poc Azolla microphylla dan Ampas Teh Terhadap Pertumbuhan dan Produktivitas Tanaman Selada (Latuca sativa L) dengan Metode Hidroponik - Triana Ambarwati; Aminah Asngad (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to determine the benefits of using a combination of POC A. microphylla and tea dregs on the growth and productivity of lettuce plants using the hydroponic method. The research method used was an experiment with a Completely Randomized Design (CRD) with 2 factors including the volume of POC administration consisting of three levels (V1=150 ml, V2=200 ml, and V3=250 ml) and the time interval for POC administration consisting of level prayer (I1=once 3 days, and I2=once 6 days). The research results show that the combination of A. mycrophylla liquid organic fertilizer and tea dregs can effectively increase the growth of lettuce plants using the hydroponic method which includes the parameters of plant height, number of leaves and wet weight of the plant. The most optimal growth of lettuce was in the V2l1 treatment (volume of 200 ml POC given at three-day intervals) with an average plant height of 14.3 cm, an average increase in the number of leaves was 9 and the plant's wet weight was 0. 26 grams. In conclusion, applying liquid organic fertilizer with a combination of A. mycrophylla and tea dregs is effective on the growth of lettuce plants. Keywords: Tea Dregs, A. Microphylla, Liquid Organic Fertilizer, Lettuce